Quality of Labor Analgesia With Dural Puncture Epidural Versus Standard Epidural Technique in Obese Parturients: A Double-blind Randomized Controlled Study. Issue 1 (22nd March 2023) - Tan, H.S.; Reed, S.E.; Mehdiratta, J.E.; Diomede, O.I.; Landreth, R.; Gatta, L.A.; Weikel, D.; Habib, A.S.
Abstract : ( Anesthesiology . 2022;136:678–687) Dural puncture epidural technique is a nested needling procedure wherein a spinal needle is passed through the epidural needle and through the dura, without the injection of intrathecal (IT) medications. Delivery of neuraxial analgesia is initiated only through the epidural catheter. Even in the absence of additional medication, dural puncture's purported advantage over standard epidural placement is the unambiguous return of cerebrospinal fluid (CSF) through the spinal needle, confirming midline placement. Dural puncture may also facilitate the transfer of epidural drugs through the dural breach to help establish onset and quality of analgesia. Evidence for the efficacy of this approach is limited with some mixed data showing no clear clinical advantage. Obese parturients are particularly susceptible to epidural failure, and also at higher risk for emergency cesarean delivery wherein well-initiated neuraxial analgesia would be a further asset to avoid general anesthesia. The ostensible advantage of improved analgesic effect with the use of dural puncture vs standard epidural technique is investigated in obese patients who have the potential to draw strong benefit from an enhanced success rate for quality analgesia given the challenges inherent to this patient population.